Minat Ibu Hamil Untuk Melakukan Vaksin Covid-19 - Lellyawaty; Rizky Vaira; Merlin Karinda (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
The Covid-19 vaccine in pregnant women provides protection to the fetus from serious diseases during the early period of life. Pregnant women refused the Covid-19 vaccination due to lack of knowledge, negative attitude towards vaccines, inexperience in vaccination, and worried about the side effects and safety of the vaccine. This study aims to determine the interest of pregnant women in the Covid-19 vaccine. A cross sectional study design with a sample of 46 pregnant women was used for this study. The sampling technique was accidental sampling and the research instrument was a questionnaire. There is a relationship between vaccine history and interest in Covid-19 vaccines in pregnant women with a p-value of 0.026. There is a relationship between vaccine information and interest in the Covid-19 vaccine with a p-value of 0.000. The importance of information on the safety and benefits of the Covid-19 vaccine needs to be clearly communicated to pregnant women so as to increase the interest of pregnant women to vaccinate against Covid-19.